(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Some of the essential geometrical properties of the lens, like bore diameter, air gap length, half-half width, magnetic flux density, projector focal length, focusing power, magnification, and spherical aberration are studied in the present work. Computational results are obtained for the geometrical properties and spherical aberration in doublet magnetic lenses by using computer programs based on the theoretical methods. In this work, increasing the distance between the lens and screen caused a linear increase in the magnification. The effective length, half-half width, and the minimum projector focal length increased the slope when the air gap width and the diameter of the lens are growing. The increase in the bore and air gap width of lens resulted in an exponential decreasing in the magnetic flux density, the maximum value of the focusing power, and the, but the most significant values of the diameter and air gap length caused a minimal effect on these properties. The increase of ampere-turns resulted in a linear increase in the magnetic flux density. Finally, the increasing in the air gap length and the diameter of the lens caused a ramp increase in the spherical aberration coefficient.